Profil Populasi Tuna Madidihang (Thunnus albacares Bonnaerre, 1880) yang Tertangkap pada Perikanan Handline di Perairan Nusa Tenggara Timur dan sekitarnya - Anakotta, Anthoinette Rosaline Fransisca; Widjaya Saputra, Suradi; Fitri, Aristi Dian Purnama; Sabdaningsih, Aninditia; Baroqi, A. Riza; Timur, Putra Satria; M. Rehatta, Beatrix (Jurnal Kelautan Tropis, 2025)
Yellowfin tuna (Thunnus albacares) is the main target of capture fisheries in various tropical waters, including Indonesia, owing to its high economic value. Global market demand increases the rate of exploitation; therefore, the size of the catch is not considered. The increasing number of fishing units led to declines in tuna stocks, catches exceeding the limit, and a dominance of catch sizes smaller than the mature gonad size (Lc < Lm), resulting in a decrease in the biomass of spawning stocks. This study aimed to examine the profile of the yellowfin tuna population in the waters of East Nusa Tenggara (NTT) by analyzing its size structure, size-at-first-catch (Lc), mortality, recruitment patterns, production trends, and Catch Per Unit Effort (CPUE). Length and weight data were obtained from I-Fish (Indonesian Fisheries Information System) initiated by YMDPI. The analysis showed that the yellowfin tuna caught ranged in size from 78 to 173 cm and were dominated by the 94-125 cm size group (82.86%). The catch consisted of 99.99% adult fish and 0.01% juveniles. The Lc value ranged from 103.34–106.55 cm, fishing mortality (F=1.44) was higher than natural mortality (M = 0.71) and the exploitation rate (E) was 0.67, indicating overfishing. Recruitment occurred throughout the year, peaking in June. Production increases in April, June, and October. CPUE ranged from 0.45-0.80 tons/trip, most fish weighed 17-23 kg (38.32%) and fish weighed more than 45 kg <1%. Overall, this condition emphasizes the importance of sustainable management based on periodic data to maintain the sustainability of the tuna population and the fisheries industry. Tuna madidihang (Thunnus albacares) merupakan target utama perikanan tangkap di berbagai perairan tropis, termasuk Indonesia, karena bernilai ekonomi tinggi. Pemintaan pasar global meningkatkan laju eksploitasi, sehingga ukuran layak tangkap tidak diperhatikan. Penurunan stok tuna disebabkan oleh, meningkatnya jumlah unit penangkapan, volume tangkapan yang melebihi batas serta dominasi ukuran tangkapan lebih kecil dari ukuran matang gonad (Lc < Lm), menyebabkan biomassa stok memijah berkurang. Penelitian ini bertujuan untuk mengkaji profil populasi tuna madidihang di perairan Nusa Tenggara Timur (NTT) melalui analisis struktur ukuran, ukuran pertama kali tertangkap (Lc), mortalitas, pola rekrutmen, tren produksi dan Catch Per Unit Effort (CPUE). Data panjang dan berat diperoleh dari I-Fish (Indonesian Fisheries Information System) yang diinisiasi oleh YMDPI. Hasil analisis menunjukan, tuna madidihang yang tertangkap berukuran 78-173 cm, didominasi oleh kelompok ukuran 94-125 cm (82,86 %). Komposisi tangkapan terdiri dari 99,99% ikan dewasa dan 0,01% juvenil. Nilai Lc berisar dari 103,34–106,55 cm, mortalitas penangkapan (F=1,44) lebih tinggi dari mortalitas alami (M = 0,71) dan laju eksploitasi (E) sebesar 0,67, mengindikasikan terjadinya overfishing. Rekrutmen terjadi hampir sepanjang tahun, puncaknya pada bulan Juni. Produksi meningkat pada bulan April, Juni dan Oktober. CPUE berkisar antara 0,45-0,80 ton/trip, sebagian besar ikan berbobot 17-23 kg (38,32%) dan ikan berukuran lebih dari 45 kg < 1%. Secara keseluruhan kondisi ini menegaskan pentingnya pengelolaan berkelanjutan berbasis data periodik untuk menjaga kelestarian populasi dan industri perikanan tuna.